Parallelization using parallel virtual machine (PVM) / Norikhti Faqriah Azime - Azime, Norikhti Faqriah (2006)
Parallelization is a process where the tasks can be distributed using Master and Slave paradigm. Parallel Virtual Machine (PVM) is a software infrastructure that emulates a generalized distributed memory multiprocessor in heterogeneous networked environment. It is an open source program which provides the capability for using a number of networked (TCP/IP) machines as a parallel virtual machine to perform the tasks. The purpose of this thesis project is to study the PVM and its significance to the users after using the software. Some researches about PVM itself have been retrieved through some books, journals, articles and also some valuable information from others. After that, the information was then divided into several parts which consist of the PVM background, PVM implementation and also its significance to the users. The second objective is to compare the time consuming of matrix calculation before and after using the PVM. Based on the findings, it is recommended to use more than two slaves in order to have a great difference of time consuming to perform the calculation. Since this project is fully tested on Linux platform, so it is suggested that the future researcher who will be continuing this project in depth may consider using multi platform such as Windows, Sun Solaris and Linux. In brief, we know that the implementation of PVM can benefits both the students as well as the lecturers other can give some contribution to the faculty generally.